Seismic performance of ancient masonry buildings: a sensitivity analysis - Mendes, N. (2013)
Ancient masonry structures are usually associated to a high seismic vulnerability, mainly due to the properties of the materials (low tensile and moderate shear strengths), weak connections between floors and load-bearing walls, high mass of the masonry walls and flexibility of the floors. For these reasons, the seismic performance of traditional masonry structures has received much attention in the last decades. This paper presents the sensitivity analysis taking into account the deviations on features of the “gaioleiro” buildings - Portuguese building typology. The main objective of the sensitivity analysis is to compare the seismic performance of the structure as a function of the variations of its properties with respect to the response of a reference model. The sensitivity analysis was carried out for two types of structural analysis, namely for the non-linear dynamic analysis with time integration and for the pushover analysis proportional to the mass of the structure. The Young’s modulus of the masonry walls, Young’s modulus of the timber floors, the compressive and tensile non-linear properties (strength and fracture energy) were the properties considered in both type of analysis. Additionally, in the dynamic analysis, the influences of the viscous damping and of the vertical component of the earthquake were evaluated. Finally, a pushover analysis proportional to the modal displacement of the first mode in each direction was also carried out. The results shows that the Young’s modulus of the masonry walls, the Young’s modulus of the timber floors and the compressive non-linear properties are the parameters that most influence the seismic performance of the structure for both sensitivity analyses. Furthermore, it is concluded that that the stiffness of the floors influences significantly the strength capacity and the collapse mechanism of the numerical model, and the strengthening of the timber floors improved significantly the seismic performance of the ancient masonry buildings with flexible floors.